Maternal dominance contributes to subgenome differentiation in allopolyploid fishes - Min-Rui-Xuan Xu; Zhen-Yang Liao; Jordan R. Brock; Kang Du; Guo-Yin Li; Zhi-Qiang Chen; Ying-Hao Wang; Zhong-Nan Gao; Gaurav Agarwal; Kevin H-C Wei; Feng Shao; Shuai Pang; et al. (Nature Communications, 2023)
Abstract Teleost fishes, which are the largest and most diverse group of living vertebrates, have a rich history of ancient and recent polyploidy. Previous studies of allotetraploid common carp and goldfish (cyprinids) reported a dominant subgenome, which is more expressed and exhibits biased gene retention. However, the underlying mechanisms contributing to observed ‘subgenome dominance’ remains poorly understood. Here we report high-quality genomes of twenty-one cyprinids to investigate the origin and subsequent subgenome evolution patterns following three independent allopolyploidy events. We identify the closest extant relatives of the diploid progenitor species, investigate genetic and epigenetic differences among subgenomes, and conclude that observed subgenome dominance patterns are likely due to a combination of maternal dominance and transposable element densities in each polyploid. These findings provide an important foundation to understanding subgenome dominance patterns observed in teleost fishes, and ultimately the role of polyploidy in contributing to evolutionary innovations.